Home page for accesible maths 6 Chapter 6 contents

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

6.42 Laplace transform of the derivative

Proposition.

Suppose that ff is as in frame 6.41 and has continuous derivative ff^{\prime}. Then the Laplace transform converts differentiaton to multiplication, so

0e-sxf(x)dx=-f(0)+0se-sxf(x)dxfor s>as>a.\int_{0}^{\infty}e^{-sx}f^{\prime}(x)\,dx=-f(0)+\int_{0}^{\infty}se^{-sx}f(x)% \,dx\;\mbox{for $s>a$}.

Proof. We integrate by parts:

0Re-sxf(x)dx=[e-sxf(x)]0R+s0Re-sxf(x)dx\int_{0}^{R}e^{-sx}f^{\prime}(x)\,dx=\,{\left[e^{-sx}f(x)\right]_{0}^{R}+s\int% _{0}^{R}e^{-sx}f(x)\,dx}
=f(R)e-sR-f(0)+s0Re-sxf(x)dx.{=f(R)e^{-sR}-f(0)+s\int_{0}^{R}e^{-sx}f(x)\,dx.}

Now by assumption, |f(R)e-sR|MeaRe-sR0|f(R)e^{-sR}|\leq{Me^{aR}e^{-sR}\rightarrow 0} as RR\rightarrow\infty.